The Philosophy of Psychiatry and Biologism - Bettina Schoene-Seifert (Frontiers Research Topics, 2014)
There has been an ongoing debate about the capabilities and limits of the bio-natural sciences as sources and the methodological measure in the philosophy of psychiatry for quite some time now. Still, many problems remain unsolved, at least partly for the following reasons: The opposing parties do not tend to speak with each other, exchange their arguments and try to increase mutual understanding. Rather, one gets the impression that they often remain in their "trenches", busy with confirming each others' opinions and developing their positions in isolation. This leads to several shortcomings: (1) Good arguments and insights from both sides of the debate get less attention they deserve. (2) The further improvement of each position becomes harder without criticism, genuinely motivated by the opposing standpoint. (3) The debate is not going to stop, at least not in the way it would finish after a suggested solution finds broad support; (4) Related to this, insisting on the ultimate aptnessof one side is just plainly wrong in almost every case. Since undeniably, most philosophical positions usually have a grain of truth hidden in them. In sum, many controversies persist with regard to the appropriate methodological, epistemological, and even ontological level for psychiatric explanation and therapies. In a conference which took place in December last year, we tried to contribute to a better understanding about what really is at issue in the philosophy of psychiatry. We asked for a common basis for several sides, for points of divergence and for the practical impact of different solutions on everyday work in psychiatry. Since psychiatry as a whole is a subject that is to wide to be covered in a single meeting, we focused on the following four core topics: 1. Competing accounts of psychiatric biologism, reductionism, and physicalism. 2. Mental disease and brain disease in the light of current neuroscientific and epigenetic findings. 3. Normative suppositions for different accounts of mental disease. 4. Normative implications of different accounts of mental disease. These topics, which have been vigorously as well as fruitfully discussed at our conference, will (ideally) be, too, in the center of our contribution to Frontiers. More precisely, we think of arranging a "research topic" which assembles the issues of the conference. At this point, it seems promising to us to group three or four Target Articles (TA) and let them get criticized by a couple of commentaries from different angles to give the issue a much broader and detailed perspective.